INTELLIGENT SUPPORT OF EDUCATIONAL PROCESSES AT LEVEL OF SPECIALITY - Irina I. Kazmina; Evgeny V. Nuzhnov (Открытое образование (Москва))
The article is devoted to intelligent support of educational processes at level of speciality with the help of information system. In this paper intelligent information system of Modern Humanitarian Academy is considered and three directions of development of intelligent support within the scope of developed information system are offered. These directions include: development of model of student, data mining of quality of teaching and prediction of quality of teaching in the future.